Digital Education at UIN Sunan Gunung Djati: A Review of Regulation, Leadership, and Institutional Development Toward World-Class University - Meira Dwi Indah Purnama; Kasful Anwar Us; Fridiyanto (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
Digital-based education has become a global paradigm that requires a comprehensive transformation in regulations, management, leadership, and institutional frameworks within higher education. This study aims to identify global issues in digital education relevant to Islamic higher education institutions; analyze UIN Sunan Gunung Djati Bandung’s strategic responses and policy adaptations to these global demands; describe internal and external challenges during the digital transformation toward a World Class University (WCU); and provide strategic recommendations for a sustainable and globally competitive digital education system. This research employs a literature review, collecting data through analysis of institutional documents, and online news tracking related to digitalization, leadership, and higher education regulations. The findings reveal that UIN Bandung addresses global challenges—such as technological disruption, digital inequality, and accreditation demands—by strengthening online learning regulations, modernizing digital-based management services, fostering transformational leadership, and establishing adaptive digital institutions. Key challenges include infrastructure limitations, uneven digital literacy, limited internationalization of digital programs, and a slow organizational cultural shift. To overcome these issues, the university implements comprehensive strategies, including strengthening digital infrastructure, reforming globally oriented curricula, enhancing digital competencies among academic communities, and promoting international collaboration. The study emphasizes that comprehensive institutional readiness is essential for UIN Sunan Gunung Djati Bandung to realize its vision as a World Class Digital University that is adaptive, ethical, and globally competitive.